Revision of Neocolochelyna Malaise (Hymenoptera: Tenthredinidae) - Niu, Gengyun; Wei, Meicai; Shinohara, Akihiko; Naito, Tikahiko (Zootaxa, 2016)
Neocolochelyna Malaise, 1937 is revised. Curvatapenis Wei, 2002 is treated as a subgenus of Neocolochelyna. The genus and its type species, N. montana Konow, 1898, as well as N. (C.) itoi Takeuchi, 1951 and N. (C.) testaceoa Wei, 2002 are redescribed based on types and new material. N. (N.) acutilabria Niu & Wei sp. nov., N. (C.) hyalina Niu & Wei sp. nov. and N. (C.) wui Niu & Wei sp. nov. are described. Neocolochelyna hakusana Togashi, 1995 is a new synonym (syn. nov.) of N. itoi Takeuchi, 1951. Neocolochelyna (Curvatapenis) testaceoa (Wei, 2002) is a new combination (comb. nov.). A key to species of Neocolochelyna is provided.